Pengaruh Disiplin Kerja Terhadap Kinerja Pegawai Puskesmas Wara Barat Kota Palopo - Mischa Patricia; Dahlia Buke; Ririn Melisa; Gusti Gusti; Ishak Runi; Erwina Erwina (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The purpose of this study was to determine the effect of work discipline on employee performance at the Wara Barat Health Center in Palopo City. The results of this study are that there is a partial positive effect between Work Discipline and Employee Performance at the West Wara Health Center in Palopo City. The test results show that the influence of the dependent variable (X) on the independent variable (Y) has a strong influence and can be proven by the coefficient of determination (R2) with a result of 0.688 = 68.8% and the remaining 31.2% is caused by the variables not examined. Work discipline has a significant effect on employee performance with a significant value of 0.00 ≥ 0.05 with a correlation coefficient value of 0.829 meaning that the relationship or correlation/with the dependent variable (X) work discipline has a very strong effect on the independent variable (Y) the performance of West Wara Health Center employees Palo City.